Carl Schmitt and the Limits of the Modern Liberal State (Economic and Political Thought, 2018)
This paper looks at Schmitt and his critique of liberalism in terms ofthe question of how the constitutional structure of the modern state canlead to certain contradictions and problems that arise out of the radicalismof the liberal doctrine advanced by the neo-Kantian legal tradition thatdominated in Germany in the early twentieth century. I argue that accordingto Schmitt a return to Hobbes, as well as other modern political thinkers suchas Machiavelli and Bodin, was the only means to correct this radicalisation ofliberalism to allow for the survival of politics.
Keywords: Carl Schmitt, Liberalism, State, Executive Power, Decisionsism, Sovereignty